ASSESSMENT OF CHANGES IN HYDROMETEOROLOGICAL PHENOMENA (A CASE STUDY OF KASHKADARYA REGION) - Bo’riyev Aktam Dilshod o’g’li (Western European Studies, 2025)
This article analyzes the trends in changes in hydrometeorological phenomena observed in the Kashkadarya region. During the study, the dynamics of temperature, precipitation, wind speed, and other indicators in the region are analyzed based on data from meteorological observation stations. The research results contribute to a deeper understanding of the region's climatic characteristics and help develop strategies for preventing natural disasters
Keywords: Hydrometeorological phenomena; Climate change Kashkadarya region; Temperature dynamics Precipitation